Effect of TiO2 and nozzle geometry on diesel emissions fuelled with biodiesel blends. Issue 5 (4th July 2019) - Gunasekar, P.; Manigandan, S.; Ilangovan, N.; Nithya, S.; Devipriya, J.; Saravanan, W. S. R.
ABSTRACT: In this present study, the compression ignition engine was designed to run on CIME ( Calophyllum inophyllum methyl ester) biodiesel with nanoparticles. The TiO2 nanoparticle is added to the biodiesel in the form of nanofluid at concentration levels of 100 ppm whereas ethanox is added at levels of 100, 200 and 500 ppm. The nanoparticle and the ethanox are dispersed by the ultrasonication process. The addition of nanofluid reduces the particulate emission like nitrogen oxide (NO x ) at 100% load. The efficiency is better and emission is reduced owing to the influence of explosion of water molecules present in the biodiesel. We found ethanox to be a superlative nanofluid to reduce the emission of toxic gas at appreciable levels. We have witnessed a 20% reduction in emission of NO x and 10% reduction of other particulate emission. In addition, the exit geometry of exhaust is modified from a circular shape to an elliptical one and the consequence of the geometry is calculated.